Guidelines for the microbiological quality of treated wastewater used in agriculture: recommendations for revising WHO guidelines - Ursula J. Blumenthal; D. Duncan Mara; Anne Peasey; Guillermo Ruiz-Palacios; Rebecca Stott (The World Health Organization, 2000)
Three different approaches for establishing guidelines for the microbiological quality of treated wastewater that is reused for agriculture are reviewed. These approaches have different objectives as their outcomes: the absence of faecal indicator organisms in the wastewater, the absence of a measurable excess of cases of enteric disease in the exposed population and a model-generated estimated risk below a defined acceptable risk. If the second approach (using empirical epidemiological studies supplemented by microbiological studies of the transmission of pathogens) is used in conjunction with the third approach (using a model-based quantitative risk assessment for selected pathogens) a powerful tool is produced that aids the development of regulations. This combined approach is more cost-effective than the first approach and adequately protects public health. The guideline limit for faecal coliform bacteria in unrestricted irrigation ( < 1000 faecal coliform bacteria/100 ml) is valid, but for restricted irrigation < 10(5) faecal coliform bacteria/100 ml is recommended when adult farmworkers are exposed to spray irrigation. A limit of < 10³ faecal coliform bacteria/100 ml is recommended if flood irrigation is used or children are exposed. The guideline limit for nematode eggs for both types of irrigation is adequate except when conditions favour the survival of nematode eggs and where children are exposed; in these cases it should be reduced from < 1 egg/l to < 0.1 egg/l.